ANALISIS GAYA BAHASA DALAM SURAH AL FATIHAH(Kajian Stalistika) - Maizar Tri Al Iqram; Ahmad Dardiri; Raswan; Achmad Fudhaili (Adisam Publisher, 2025)
Surah al-Fatihah was chosen because it has a unique and interesting style of language that can be discussed from a phonological perspective. This research is qualitative in nature with a descriptive analysis method that begins by describing the aspects of the beauty of the sound of the Qur'an, starting from Arabic vowels and consonants to the characteristics of the Hijaiyah letters. This study employs theories of phonology, rhythm, and musicality of the Qur'an, as well as theories of sound beauty.